(untitled) (Bulletin of criminological association of Ukraine, 2025)
The article is devoted to the criminological analysis of human trafficking in Ukraine. The values of the dynamics of reproduction of human trafficking for 2015–2024 allow us to identify sinusoidal fluctuations with an interval of 1 year. The only exception is the period 2015–2017, in which the level has been increasing for two years (2016 and 2017). The remaining years of the dynamics series alternately demonstrate an increase and decrease in the level without a general pronounced trend. The average value of the series is 198 crimes. The criminal-law structure of human trafficking indicates the severity of this crime, the highly dangerous nature of criminal practices. Directly in the structure of criminal offenses provided for in Art. 149 of the Criminal Code of Ukraine, those prevail, the features of the composition of which are fixed in Part 2 of this article. At the same time, it is worth emphasizing the dynamic changes in the structure, which, although they do not show a stable trend, are less evident in the episodic increase in the share of especially qualified elements in the structure of criminal offenses provided for in Article 149 of the Criminal Code of Ukraine, which is almost never recorded on a significant scale by the indicator of the main element of the crime. A relatively high share of group criminal activity in the structure of human trafficking is recorded.